PELATIHAN FOTOGRAFI PRODUK DI BANK SAMPAH GULON ASRI SURAKARTA - Murni, Endri Sintiana; Nufut Alimin, Nurhayatu; Yunianti, Esterica (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Garbage banks have the potential to increase people's income. Where the waste bank can turn waste into useful items. Products made by waste banks are diverse, both in the form of accessories and crafts. The production of product waste is already good and useful. The member of the waste bank can make attractive products to fulfil the demand of the public. But in terms of selling their products, the waste bank doesn't really understand what kind of attraction is suitable to make their products sell. To overcome these problems, direction is needed using product photography which can increase the selling value of the product. This training aims to improve the community's ability to manage their products with product photography that can increase selling power. The method in this service is the mentoring method. The mentoring was conducted at the Gulon Asri Garbage Bank, Jebres, Surakarta. This training focuses on fostering the creativity of residents to make product photography with smartphones so that it is hoped that it can help residents sell their work from the Gulon Asri Waste Bank to become more attractive through social media.